Tax Competition in a Fiscal Union with Decentralized Leadership - Marko Koethenbuerger (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper examines capital tax competition in the presence of an interstate transfer policy without federal commitment. Lack of commitment implies that tax policy is chosen prior to federal transfers. The paper's main result is that ex-post federal policy internalizes horizontal fiscal externalities, insulating tax policy from capital mobility. Federal policy, however, introduces a new source of inefficiency unrelated to tax competition. Specifically, ex-post transfer payments prove to be equivalent to an interstate revenue-sharing system which may render federal intervention in the presence of fiscal externalities welfare-deteriorating relative to tax competition.
Keywords: 330; federalism; capital tax competition; commitment; soft budget constraints